Administracyjnoprawne instytucje kształtowania i kontroli jakości wyrobów: [Administrative law instruments of influencing and control of quality of goods] (Studia Prawnicze / The Legal Studies, 1980)
The article deals with the administrative law measures the function of which is to secure adequate quality of goods. Measures applied to specific goods, such as e.g. farmaceutical products, food-stuffs, seeds, equipement or products of noble metals are also discussed.Control of both commercial entreprises and producers is fulfilled not only by higher-level units but also by the units of state administration such as: Polish Committee of Normalization, Measurements and Quality, Sanitary Inspection Office, Seeds Inspection Office, Inspection of Commerce Office and Ministers of Agriculture, Health and Social Welfare. A significant role of R and D units civic organizations should also be stressed.One can distinguish several typical legal measures applied by state administration organs in quality control. These are: permissions to start production, defining necessary characteristic of the products, approval of the models of products, issuing quality certificates, permissions to bring a product into commerce, orders to stop production, orders to destroy existing goods, prohibitions to buy and to sell. The above mentioned measures have different legal character. The majority constitute administrative acts, however, we can also distinguish normative acts and statements having the character of certificats. The majority of administrative law measures is to secure the minimum and not the maximum quality standard of products. They are applied first of all in case of products, the estimation of which by a consumenr is difficult in practice and the damages caused by unsuitable quality hardly commensurable with the value of the goods themselves.